(untitled) (Bangladesh Journal of Agricultural Research, 2009)
In vitro organogenesis of a lowland species of Colocasia esculenta sp. esculenta L. cv. Latiraj was assessed in relation to explant types (meristem, parenchymatous tissues and storage tissues); three levels of each of NAA, BAP, Kn, and 2,4-D; four culture environments, such as 16h 3000 lux light intensity, 24±2°C, 24h dark + 24±2°C, 24h dark + 30±3°C, and 12h diffuse light + 30±3°C. Only isolated meristem and parenchymatous tissues regenerated plants with various degree of morphogenic intensity with different combinations of growth regulators. Meristem under both light and dark and at 24±2°C with upto Kn 3.0 + NAA 3.0 showed proliferation with poor rate of growth, while Kn 1.0+ NAA 3.0 had comparatively good response. The parenchymatous tissues with above environments responded very quickly with varying degree of growth intensity. Kn+2,4-D was found least effective on regeneration from any explants. NAA and BAP had an effect on proliferation of shoot, root and other growth characters from both meristem and parenchymatous tissues under both light and dark conditions at 24±2°C. This combination showed a very high degree of proliferation and caused callusing to some extent when cultured at dark which developed shoots and roots quickly after transferring to light. Except NAA+BAP, no other combination formed stolon. The white colour storage tissues after 30 days turned yellowish followed by greenish with shiny pimples after 50 days indicating that the cultures with protocorm may be developed. Almost all the cultures under high temperature environments (30±3°C) neither survived nor proliferated. The meristems also died within 15-20 days, while others within 25-30 days. Thus, a temperature range of 30±3°C was in no way suitable for in vitro culture of lowland species of Colocasia esculenta cv. Latiraj. Key Words: Organogenesis, auxins, cytokinins, meristem, parenchymatous tissues, storage tissues, Colocasia esculenta L. cv. Latiraj. DOI: 10.3329/bjar.v34i3.3963 Bangladesh J. Agril. Res. 34(3) : 385-394, September 2009